Bio‐interface behaviour of graphene and semiconducting SWCNT:C60 blend based nano photodiode for subretinal implant. Issue 2 (24th June 2020) - Meyyappan, Moorthy Vijai; Parthasarathy, Varadarajan; Daniel, Rathnasami Joseph
Abstract : Hybrid interfaces between living cells and organic conjugated polymers play a pivotal role in bioelectronics medicine. Currently, conjugated polymers are widely utilised for optical stimulation of living cells and other bio‐interface applications such as neural probes, cellular scaffolds and biosensors for drug release. In such a work, the authors fabricated and characterised the Nano Photodiode array device for the subretinal implant. However, the authors did not discuss in their report about the biocompatibility of this new device. In this work, the authors manifest that the quintessential graphene electrode and polymer blend of semiconducting single‐wall carbon nanotube and C60 fullerene (S‐SWCNT:C60 ) sustains its optoelectronic properties all through the various strides for neural preparation. Further, the studies show that these materials can provide a favourable environment for cell proliferation and a high degree of biocompatibility. PC‐12 cells used as a valuable model to validate the biocompatibility were grown successfully onto the S‐SWCNT:C60 active layer still preserving its optical and electrical properties. The improved electrical performance of nano photodiode made of graphene, S‐SWCNT:C60 established in the previous studies and the excellent bio‐interface performance of this nano photodiode shows that the nano photodiode array proposed by the authors is a strong candidate for subretinal implants.